The Critical Success Factors for Implementation of CRM and Knowledge Management in a Work Setting - Faed, Alireza; Radmand, Pedram; Talevski, Alex (IEEE Computer Society, 2010)
Customer Relationship Management is the most vigorous tools in our era and is the integration of trust, business and technology to gratify the requirements of the clients. CRM is a strategy of dealing with people, technology and process and need to be implemented precisely. CRM is the most outstanding business strategy that consolidates internal procedures and externals to generate and convey value to the spotted customers and CRM can easily neutralize competitive perils, provide a good source of roadmap for the company and customers. Moreover it may clarify the potential pitfalls in creating success for the company.CRM involves validating and evaluating critical success factors, which cover the three perspectives of CRM as the theoretical base, and which constitute a guide for companies in the implementation of the applications. Due to this, the desired benefits have intensified customer satisfaction and maintenance, by generating personalized products and value-added services. In this paper, the author investigates the factors that can positively leverage the implementation and use of CRM and creates differentiation among these factors and knowledge management factors. What is more, the paper aims at determining technical feature between CRM and knowledge management and managed to compare KM with CRM successfully.